2021
DOI: 10.1186/s12871-021-01462-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of myocardial and acute kidney injury following radical nephrectomy with vena cava thrombectomy: a retrospective cohort study

Abstract: Background Radical nephrectomy with thrombectomy is the mainstay treatment for patients with renal cell carcinoma with vena cava thrombus. But the procedure is full of challenge, with high incidence of major complications and mortality. Herein, we investigated the incidence and predictors of myocardial injury and acute kidney injury (AKI) in patients following radical nephrectomy with inferior vena cava thrombectomy. Methods Patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Several studies have shown that damage to the renal vessels is one of the most common injuries during performing radical nephrectomy in the treatment of RCC. 1 , 4 Fortunately, no damage occurred to the kidney tissue and the main vessels around the mass in our patient.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have shown that damage to the renal vessels is one of the most common injuries during performing radical nephrectomy in the treatment of RCC. 1 , 4 Fortunately, no damage occurred to the kidney tissue and the main vessels around the mass in our patient.…”
Section: Discussionmentioning
confidence: 54%
“…Troponins were studied in relationship with RCC, as well. A retrospective study reported that myocardial injury occurred in 38.8% and AKI in 42.7% of patients following nephrectomy with inferior vena cava thrombectomy [27]. Levels of cTn I were significantly higher in patients with these complications [27].…”
Section: Cardiac Biomarkersmentioning
confidence: 99%
“…A retrospective study reported that myocardial injury occurred in 38.8% and AKI in 42.7% of patients following nephrectomy with inferior vena cava thrombectomy [27]. Levels of cTn I were significantly higher in patients with these complications [27]. In general, troponin has been demonstrated to increase in systemic RCC treatment.…”
Section: Cardiac Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation